(untitled) (Global Psychiatry Archives, 2026)
Objectives: Mixed depression remains poorly operationalised in current nosologies, leading to misclassification and suboptimal treatment. We propose a two-subtype framework—Bipolar-Expansive Depression (BXD) and Unspecific-Excitative Depression (UXD)—to improve recognition and guide safer treatment choices. Methods: Narrative synthesis of historical accounts, critiques of DSM-5 and ICD-11, Koukopoulos’ concepts, the ISBD Task Force report (2022), validation of the Shahin Mixed Depression Scale (SMDS), and introduction of the Shahin Activated Depression Screener (SADS). Results: BXD combines depressive mood with expansive/energised features (pressured speech, goal-directed bursts, racing thoughts, reduced need for sleep). UXD presents depressive mood with excitatory distress (agitation, irritability, inner tension, motor restlessness, mood lability, crowded/racing thoughts). SMDS has been validated for non-DSM excitatory features. SADS is under development and has not yet been validated. Conclusions: Recognising BXD and UXD refines the concept of mixed depression, addressing DSM-5/ICD-11 gaps and improving patient care.